A conceptual model and technological support for organizational knowledge management - Ale, Mariel Alejandra (2014)
Knowledge Management (KM) models proposed in the literature do not take into account all necessary aspects for effective knowledge management. First, to address this issue, this paper presents a set of requirements that any KM model or initiative should take into account to cover all aspects implied in knowing processes. These requirements were identified through a critical and evolutionary analysis of KM. Second; the paper presents a new distributed KM Conceptual Model whose building blocks are the knowledge activities involved in knowing processes. These activities are: knowledge creation, knowledge sharing, and knowledge representation and retrieval. This model provides a holistic view of KM whose purpose is helping managers understand the scope of this initiative, and supplying a guide for research and implementation in organizations. In this sense, the model presents KM as a highly social rather than technological process. Third; the paper briefly describes an architecture to provide a technological support for knowledge representation and retrieval activities of the proposed KM Conceptual Model. This architecture allows implementing a distributed organizational memory that helps to represent the knowledge context through an ontological model, providing a local perspective of each knowledge domain within the organization. Strategies for knowledge annotation, knowledge retrieval, and ontology evolution are briefly described and results of preliminary performance analysis are shown. Finally; based on the available literature, a comparative analysis of different KM models shows their adequacy for previously presented requirements.